Influence of Green Marketing Strategies on Consumer Behavior - Kuria, Bonface (International Journal of Marketing Strategies, 2024)
Purpose: The aim of the study was to assess the influence of green marketing strategies on consumer behavior. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Research on the influence of green marketing strategies on consumer behavior reveals several key findings. Firstly, consumers increasingly prioritize environmentally friendly products and companies, driven by concerns about sustainability and climate change. Green marketing strategies, such as eco-labeling, eco-packaging, and messaging emphasizing environmental benefits, significantly influence consumer perceptions and purchasing decisions. Studies indicate that consumers are willing to pay a premium for products perceived as environmentally friendly, particularly when accompanied by credible certifications or endorsements. Additionally, consumers tend to exhibit greater brand loyalty to companies perceived as environmentally responsible. However, the effectiveness of green marketing strategies can vary depending on factors such as consumer demographics, product characteristics, and the perceived sincerity of the company's environmental efforts. Overall, the findings underscore the significant impact of green marketing on shaping consumer behavior and highlight the importance for companies to integrate sustainable practices into their marketing strategies to meet evolving consumer preferences and contribute to environmental conservation efforts. Implications to Theory, Practice and Policy: Theory of planned behavior, diffusion of innovation theory and cognitive dissonance theory may be use to anchor future studies on assessing the influence of green marketing strategies on consumer behavior. Businesses should prioritize authentic and transparent green marketing strategies that resonate with consumer values and preferences. Governments and regulatory bodies should enact policies that incentivize and promote green marketing practices among businesses.